2017
DOI: 10.2174/1567201813666160502142856
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Ciclopirox Olamine after Buccal Administration in Rabbits

Abstract: The experiment suggests that oral mucoadhesive film may be a valuable alternative ciclopirox olamine administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Pharmacokinetic experiments have previously shown that CPX's half-life in the organism is short, with strong affinity for serum albumin and fast catabolism mediated by a glucuronidation reaction (37,38). We found that glucuronidation occurred at the hydroxyl moiety and that CPXglu was incapable of reducing porphyrins in the CEP cellular models (Fig.…”
Section: Preliminary Pharmacokinetics and Dose-response Studiesmentioning
confidence: 69%
See 1 more Smart Citation
“…Pharmacokinetic experiments have previously shown that CPX's half-life in the organism is short, with strong affinity for serum albumin and fast catabolism mediated by a glucuronidation reaction (37,38). We found that glucuronidation occurred at the hydroxyl moiety and that CPXglu was incapable of reducing porphyrins in the CEP cellular models (Fig.…”
Section: Preliminary Pharmacokinetics and Dose-response Studiesmentioning
confidence: 69%
“…2G). To quantify the effective concentration of CPX administered within the pellets, we have developed an NMR-based method for the analysis of the active and glucuronide forms of CPX in serum and urine (see Materials and Methods) and cross-validated it against the most conventional HPLC-based method (38). The average concentration of active CPX in serum was CPX = 2.79 ± 0.6 mM and CPXglu = 12 ± 1.2 mM, which is equivalent to an intake (gavage) of 300 mg/m 2 and close to the toxicity limit for the drug (39).…”
Section: Preliminary Pharmacokinetics and Dose-response Studiesmentioning
confidence: 99%